Neuropathogenesis of HIV and emerging therapeutic targets. (3rd July 2022) - Siddiqui, Alina; He, Celestine; Lee, Gina; Figueroa, Alex; Slaughter, Alexander; Robinson-Papp, Jessica
ABSTRACT: Introduction: HIV infection causes a wide range of neurological complications, many of which are among the most common complications of chronic HIV infection in the era of combined antiretroviral therapy. These neurological conditions arise due to complex interactions between HIV viral proteins and neuronal and glial cells that lead to the activation of various inflammatory and neurotoxic pathways across the nervous system. Areas Covered: This review summarizes the current literature on the pathogenesis and clinical manifestations of neurological injuries associated with HIV in the brain, spinal cord, and peripheral nervous system. Molecular pathways relevant for possible therapeutic targets or advancements are emphasized. Gaps in knowledge and current challenges in therapeutic design are also discussed. Expert Opinion: Several challenges exist in the development of therapeutic targets for HIV-associated cognitive impairments. However, recent developments in drug delivery systems and treatment strategies are encouraging. Treatments for HIV-associated pain and peripheral sensory neuropathies currently consist of symptomatic management, but a greater understanding of their pathogenesis can lead to the development of targeted molecular therapies and disease-modifying therapies. HIV-associated autonomic dysfunction may affect the course of systemic disease via disrupted neuro-immune interactions; however, more research is needed to facilitate our understanding of how these processes present clinically.